Spinal Epidural Extraskeletal Ewing Sarcoma: MR Findings in Two Cases - Hoon Shin, Ji; Kyu Lee, Ho; Chul Rhim, Seung; Cho, Kyung-Ja; Gon Choi, Choong; Chul Suh, Dae (American Journal of Neuroradiology, 2001)
Summary: We report the CT myelography and MR findings of two cases of extraskeletal Ewing sarcoma involving the spinal epidural and paravertebral spaces in a middle-aged man (case 1) and a young woman (case 2). In both cases CT myelography showed epidural and paravertebral masses on one side, with widening of the ipsilateral neural foramina at the C5–C6 level in case 1 and at the C7–T1 level in case 2. On MR images, the masses were isointense to muscle on T1-weighted images, hyperintense on T2-weighted images, and showed moderate enhancement on contrast-enhanced T1-weighted images. In one case, all pulse sequences showed linear signal voids, representing the vertebral artery encasement within the mass. The intradural component connected with the main mass was detected in the other case.